Influence of different approaches to training of main movements on physical fitness of 4 years boys with various motor asymmetry - L. L. Galamandjuk (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: determination of effectiveness of different training main movements' methods in physical fitness improvement of boys with different manual motor asymmetry. Material: 50 boys with ambidexterity (4 years old age) took part in the research. There was used the following: oral questioning, dynamometry and methodic by M.M. Bezrukikh. Results: usage of one of variants of "symmetric" approach determines specificities of motor qualities' development: among boys with ambidexterity in motor asymmetry variant "first with passive hand, then with active one" and variant "first with active and then with passive hand" ensure improvement of all tested qualities (except flexibility and quickness). Boys with right orientation of manual motor asymmetry demonstrated improvement of all qualities (except coordination in ballistic movements for accuracy, fulfilled by right arm) in the first variant. In the second variant all qualities (except already mentioned quickness) are improved. Conclusions: with any orientation of manual motor asymmetry the necessary condition of high activity and successful child's training is development of interaction between cerebral semi-spheres. Coordinated movements by left and right arms strengthen such interaction. That is why it is purposeful to consequently fulfill every movement by every arm and by two arms simultaneously.